Unveiling the Impact of JKN: Easing Financial Burdens for Pregnant Women in Indonesia - Sulaeman, Januar; Qibthiyyah, Riatu Mariatul (UI Scholars Hub, 2024)
Indonesia’s maternal mortality rate is the second highest in the ASEAN, partly due to financial barriers preventing adequate care during pregnancy and childbirth. The National Health Insurance (JKN) scheme, which is the embodiment of universal health coverage (UHC), was designed by the Indonesian government to reduce the financial risk of its participants. However, its impact on out-of-pocket health spending for pregnant women is under-researched. Using propensity score matching (PSM) and 2019 SUSENAS data, this study found that JKN membership significantly reduced out-of-pocket health spending for pregnant women—especially in eastern Indonesia, where poverty and healthcare access represent critical issues.